Performance of backfill materials under impulse and AC testings - Mileo, Vanessa Carolina Laverde; Ab Kadir, Mohd Zainal Abidin; Gomes, Chandima (IEEE, 2012)
This paper focuses on the behaviour of dry sand, bentonite and cement under different voltage conditions. These three materials play important role in electrical grounding systems, in controlling ground impedance of an electrode. However, most often the low frequency earth resistance measurements of grounding electrodes encased in these materials have been considered as the performance indicator. It has been found in this study that the behaviour of materials grossly depends on the applied voltage waveform and repetition of application or duration of the waveform. Time to breakdown in the case of bentonite is considerably smaller than that of cement. Bentonite also shows breakdown in two phases, in the voltage time curve. In cases of both bentonite and dry sand, fulgurites were formed in the application of short duration alternative voltage at 50 Hz. As fulgurites are very high in resistance compared to the original material, the overall resistive and inductive behaviours of the earth electrodes may change in the presence of leakage currents in MV and HV systems.